Global Jobs Indicators Database (JOIN) Manual Methodology and Quality Checks - Weber, Michael (The World Bank, 2021)
The Global Jobs Indicators Database (JOIN) provides information on labor market outcomes from countries across all income groups with a focus on low- and middle-income countries. The sources are in most cases Labor Force Surveys (LFSs), but other types of household surveys that include labor market information are also added. The information on the different labor market outcomes is disaggregated by gender, urban or rural area, age group of worker, and education level. All indicators are derived from a World Bank repository of harmonized household surveys. The indicators can be subsumed into four topics: sociodemographics, labor force and employment status, employment by sector and occupation, and labor market outcomes, including earnings. To ensure data reliability, a series of quality checks to both the indicators and the micro-data at the cross-sectional survey level and at the survey time-series level are conducted. Results are, among others, corroborated using statistics provided by the International Labour Organization (ILO) or the World Bank's World Development Indicators (WDI) as well as through outlier detection and consistency checks. As a result, JOIN provides only indicators for surveys that surpassed a quality check threshold. JOIN contains about 1,430 household surveys conducted in 160 countries. A JOIN benchmarking tool enables further customization options including interactions of key indicators for more granular analysis. This tool allows users to compare the labor market in their country of interest to a series of up to 10 other countries. Together, JOIN, the JOIN benchmarking tool, and the entire Jobs Diagnostic toolkit enable a thorough analysis of the labor market supply side at both a nationally aggregated level and the micro level